Chile entre el si el no - Varas, Florencia (La Epoca, Melquiades, 1988)
Entrevistas a Andrés Allamand, Clodomiro Almeyda, Jorge Insunza, Ricardo Lagos, Pablo Rodrıguez, José Tomás Sáenz y Gabriel Valdés.